2012
DOI: 10.2106/jbjs.k.01710
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically Pertinent Anatomy of the Anterolateral and Posteromedial Bundles of the Posterior Cruciate Ligament

Abstract: Background:The clock-face method to identify the femoral posterior cruciate ligament (PCL) attachment has poor accuracy and reproducibility. iVleasurements of clinically relevant anatomic structures would provide more useful surgical guidance. The purpose of the present study was to describe the attachments of the anterolateral and posteromedial bundles of the PCL relative to relevant landmarks to assist with arthroscopic anatomic PCL reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
224
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(236 citation statements)
references
References 35 publications
4
224
1
7
Order By: Relevance
“…Anatomic studies have shown that the tibial attachment of the PCL is substantially more compact than the femoral attachment; therefore a single tibial tunnel and 2 femoral sockets are hypothesized to allow good restoration of the anatomy of the native PCL. 7 Biomechanical studies have shown that the key determinant in controlling posterior tibial laxity in anatomic PCLR is the femoral tunnel placement on the medial wall and roof of the intercondylar notch. 18 Consequently, a trifurcate graft is the construct of choice for surgeons performing both open 19 and arthroscopic tibial inlay 9,20 PCLR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anatomic studies have shown that the tibial attachment of the PCL is substantially more compact than the femoral attachment; therefore a single tibial tunnel and 2 femoral sockets are hypothesized to allow good restoration of the anatomy of the native PCL. 7 Biomechanical studies have shown that the key determinant in controlling posterior tibial laxity in anatomic PCLR is the femoral tunnel placement on the medial wall and roof of the intercondylar notch. 18 Consequently, a trifurcate graft is the construct of choice for surgeons performing both open 19 and arthroscopic tibial inlay 9,20 PCLR.…”
Section: Discussionmentioning
confidence: 99%
“…This method devised by the senior author appears to be reliable and reproducible but has not yet been validated for PCLR. A recent cadaveric study has provided quantitative measurements of tunnel positions from arthroscopic landmarks that can be used for a direct measurement technique, 7 although in contrast to ACL reconstruction, 23 no in vivo studies are available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more anterior aspect of the ALB is noted by the trochlear point, whereas its more inferoposterior aspect is delineated by the medial arch point. Likewise, the PMB is located along the wall of the notch and distal to the medial arch point 12 ( Fig 2). The femoral attachments of the ALB and PMB are then marked with an arthroscopic coagulator (Smith & Nephew, Andover, MA).…”
Section: Surgical Techniquementioning
confidence: 99%
“…Next, a guide pin is drilled, entering the anteromedial aspect of the tibia approximately 6 cm distal to the joint line, e150 centered between the anterior tibial crest and the medial tibial border, and exiting posteriorly at the center of the PCL tibial attachment along the previously described PCL bundle ridge, which has been reported to be located between the ALB and PMB on the tibia. 12 Intraoperative anteroposterior and lateral radiographs or fluoroscopy is used to verify tibial pin placement, which on the lateral radiograph should be approximately 6 to 7 mm proximal to the champagne-glass drop-off at the PCL facet on the posterior part of the tibia (Fig 5). On anteroposterior radiographs, this point is identified at the medial aspect of the lateral tibial eminence and 1 to 2 mm distal to the joint line.…”
Section: Surgical Techniquementioning
confidence: 99%